Creating Cloud Storage Server Using Linux Ubuntu With File-Over Cluster Method - Anis Mirza; Melani Dewi Lusita; Munich Heindari EKasari (Journal of Information System, Informatics and Computing, 2022)
The problem that exists at PT Sewiwi Indonesia today is that there is no centralized data storage place for company files that can be accessed anywhere. And there is no data backup in the company's storage area. Cloud Storage is a form of cloud computing but is centered on data storage media, but in cloud storage there is a possibility. The problem that exists at PT Sewiwi Indonesia today is that there is no place to store data for company files that are centralized and can be accessed anywhere. And there is no data backup in the company's storage area. Cloud Storage is a form of cloud computing but is centered on data storage media, but in cloud storage there is the possibility of losing data on a small or large scale. This could be due to natural disasters, human error, or the age of the device. To overcome the existing problems, a system is needed that can store data online and a backup is needed to back up the main device in data storage. Therefore, the researcher designs and implements a cloud storage server with the failover cluster method. This system can be used as employee data storage as well as backup data that can be accessed online.